Mobbing in the Academe: The Case of Albanian Universities - Buka, Migena; Karaj, Theodhori (Mediterranean Journal of Social Sciences, 2012)
Mobbing is a new concept studied in the organizations, yet it is believed to have existed long before they gave it aname. Leymann (1996) introduced it for the first time, and since then the studies over the phenomenon have expanded. Thepresent study deals with the mobbing in the workplace, in Albania. The study aims at establishing a prevalence of thisphenomenon in academia, with no distinction whether it is a public or private institution. Other international studies have statedthat universities and are the main ground where mobbing especially flourishes. To the researcher’s knowledge there are nostudies to estimate the prevalence of mobbing in Albania. Moreover, it was looked into a correlational relation between mobbingand various consequences, such as turnover intentions, as well as psycho-somatic consequences. Based on other researchers’experiences, it was chosen to use self report questionnaires. 100 questionnaires were distributed to full time lecturers in variousuniversities around Albania. The Negative Act Questionnaire was the instrument to measure mobbing and there were questionsabout different symptoms experienced and the medical expenditures. The percentages were calculated based on Leymann’sdefinition about mobbing (at least once a week, for six months or more). The consequences of this phenomenon as expressed inphysical, psychological symptoms are calculated and discussed.